Analisis Dampak Transportasi Online terhadap Transportasi Becak dan Meningkatkan Pendapatan Pengemudi Becak di Kota Surakarta - Muhammad Zharfan Dzimar; Muzakar Isa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims is to analyze the impact of online transportation on becak transportation and increase the income of becak drivers in Surakarta City. This type of research uses quantitative method. This research uses primary data. The data collection technique in this research is a questionnaire. The population in this study are those who have characteristics who have used online transportation modes and becak transportation modes, and who have never used online transportation modes or becak transportation modes. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The result of this study is that tariffs do not have a significant influence on becak drivers' income. The number of passengers has a significant influence on becak drivers' income. Working hours have a significant influence on pedicab drivers' income.